(untitled) (Biological Sciences - PJSIR, 2004)
Animal samples include two different types of snakes, frog and five different types of fishes. The flesh, bones, scales and heads of the animals were separated and analysed for moisture, ash and minerals. The minerals, were not detected from any sample. Cu, Cd, Pb, Co and Cr. The moisture content was generally low. The ash was consistently highest in the bone but consistently lowest in flesh among the fish and in the scale among the snakes. The concentration of the minerals was highly varied among the body parts. The Ca/P ratios ranged from excellent to poor. The Na/K ratios were generally on the high side ranging between 0.55-1.05. The mineral safety index was generally good for Na, P, Mg and Ca, poor for Fe but very bad for Zn. It is an indication that the samples were contaminated by Fe and Zn.